2020
DOI: 10.33367/psi.v5i2.1036
|View full text |Cite
|
Sign up to set email alerts
|

Quarterlife Crisis Pada Masa Dewasa Awal di Pekanbaru

Abstract: The transition from adolescents to adult challenges is different from the challenges of life in the previous development process. Towards the age of 25, individuals face a new life such as work, marital status, and mindset. The quarter-life crisis is a phenomenon that is common in individuals aged 20-30 years old. The crisis of a quarter of a century, that's how the term counts with individuals who attend 25 years. The quarter-life crisis experiences’ by individuals grew up. This research is descriptive quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 1 publication
0
15
0
16
Order By: Relevance
“…It was concluded that there were several factors that influenced the emergence of the Quarter Life Crisis LC in the millennial generation, namely (1) the influence of social media (2) educational background, (3) current job, (4) family support, (5) environmental demands, and (6) alignment between personal desires and environmental demands. Furthermore, a study conducted by Herawati & Hidayat (2020) regarding the quarter life crisis in early adulthood in the new week. The results of this study indicate that the factors that affect the Quarter Life Crisis include gender, status and occupation.…”
Section: Pendahuluanmentioning
confidence: 99%
“…It was concluded that there were several factors that influenced the emergence of the Quarter Life Crisis LC in the millennial generation, namely (1) the influence of social media (2) educational background, (3) current job, (4) family support, (5) environmental demands, and (6) alignment between personal desires and environmental demands. Furthermore, a study conducted by Herawati & Hidayat (2020) regarding the quarter life crisis in early adulthood in the new week. The results of this study indicate that the factors that affect the Quarter Life Crisis include gender, status and occupation.…”
Section: Pendahuluanmentioning
confidence: 99%
“…Tema ketiga adalah circle pergaulan akan mempengaruhi keinginan individu agar mendapatkan pengakuan. Pada masa remaja akhir menuju masa dewasa awal inividu memiliki peluang yang besar dalam mengeksplorasi diri akan tetapi juga menghadapi tantangan yang besar (Herawati & Hidayat, 2020). Usia mahasiswa tingkat akhir berkisar 20 tahun keatas, pada usia ini menurut infodatin reproduksi remaja telah masuk usia dewasa (Kementerian Kesehatan RI, 2017).…”
Section: Tema 3 Pengakuanunclassified
“…Masa remaja merupakan masa peralihan setelah masa kanak-kanak yang akan menuju kepada masa dewasa. Masa dewasa terbagi menjadi 3 tahap ialah; masa dewasa awal, masa dewasa menengah, dan masa dewasa akhir (Herawati & Hidayat, 2020). Akan tetapi pendapat piaget dalam Eni Lestarina (Lestarina, Karimah, Febrianti, Ranny, & Herlina, 2017) bahwasannya dalam masa perkembangan remaja dan dewasa merupakan tingkatan yang sama, dalam hak, integrasi dalam masyarakat (dewasa), banyak memiliki aspek, menginjak kepada masa puber, memiliki ranah intelektual yang mecolok, serta memiliki ciri khas berfikir remaja dalam hubungan sosial.…”
Section: Tabaruj (Berlebih-lebihan)unclassified